APLIKASI PEMESANAN TIKET MASUK DAN TIKET WAHANA DENGAN MENGGUNAKAN QR CODE PADA WISATA DIANA WATERPARK - Jaharuddin; Selao, Ahmad; Sahidin, Sudirman; Masnur (Jurnal Manajemen dan Teknologi Informasi, 2025)
This study aims to design a QR-based ticket booking application at Diana Waterpark, which is expected to increase operational efficiency and improve visitor experience. Using a quantitative descriptive approach, data were collected through questionnaires distributed to 30 respondents who visited Diana Waterpark. The results of the application design indicate that the use of QR technology can reduce visitor waiting time and speed up the ticket booking process. In addition, this application is designed to provide convenience for users with an intuitive interface and fast booking system. However, this study also identified several areas that need to be improved, such as the ticket information management system and improving transaction security features. Overall, the design of this application is expected to have a positive impact on visitor satisfaction and loyalty, as well as provide practical solutions in ticket and ride management at Diana Waterpark. This study recommends that managers continue to develop applications with a focus on improving security systems and more integrated application features.